2016
DOI: 10.1089/jop.2015.0147
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase 1 Dose Escalation Study to Evaluate Safety, Tolerability, and Pharmacokinetics of Trabodenoson in Healthy Adult Volunteers

Abstract: Purpose: To investigate the safety, tolerability, and pharmacokinetics of trabodenoson, a highly selective adenosine mimetic targeting the adenosine A1 receptor.Methods: In Part 1, 60 healthy adult volunteers were randomized to 14 days of twice-daily topical monocular application of placebo or trabodenoson (200, 400, 800, 1,600, 2,400, or 3,200 μg). In Part 2, 10 subjects were randomized to placebo or 8 escalating doses of bilateral trabodenoson (total daily doses: 1,800–6,400 μg).Results: The incidence of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…[21][22][23][24][25] Trabodenoson is an adenosine receptor agonist with a strong selectivity for A 1 R, 30 and an established safety profile that has demonstrated exceptional tolerability, including no significant burning or stinging, and no clinically significant treatment-related systemic adverse events. 19 Data from the present study support the notion that preconditioning of the A 1 R is a feasible therapeutic strategy to reduce DED-associated ocular inflammation and exerts anti-inflammatory and cyto-protective effects on the lacrimal gland and conjunctival goblet cells.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…[21][22][23][24][25] Trabodenoson is an adenosine receptor agonist with a strong selectivity for A 1 R, 30 and an established safety profile that has demonstrated exceptional tolerability, including no significant burning or stinging, and no clinically significant treatment-related systemic adverse events. 19 Data from the present study support the notion that preconditioning of the A 1 R is a feasible therapeutic strategy to reduce DED-associated ocular inflammation and exerts anti-inflammatory and cyto-protective effects on the lacrimal gland and conjunctival goblet cells.…”
Section: Discussionsupporting
confidence: 82%
“…Trabodenoson is well-tolerated without instillation pain or irritation associated with currently approved therapies. 19 In DED is a common ocular surface inflammatory disease that results in eye discomfort and visual disturbance and can affect a patient's quality of life. Two major types of DED, as identified by the International Dry Eye Workshop are aqueous-deficient dry eye and evaporative dry eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a preliminary Phase 1 dose escalation study in 60 healthy adult volunteers, it was shown to be safe and well tolerated up to 3.2 mg per eye with no detectable systemic effects (14 days of twice-daily topical monocular application). It lowers IOP by augmenting the primary outflow pathway for aqueous humor through the trabecular meshwork [15]. , although it seems to be present in the retina and the anterior eye.…”
Section: Iopmentioning
confidence: 99%
“…A 3 agonists reduce AH flow by inhibiting chloride ion channels in ciliary epithelial cells [165]. An A 1 agonist in phase III trials has demonstrated favorable toxicity profiles, possible neuroprotective effects, and efficacious IOP lowering [166]. Receptor activation has also been shown to induce the secretion of MMPs, particularly MMP-2, probably the cause of reduced outflow resistance [167,168].…”
Section: New Classes Of Drugmentioning
confidence: 99%